RETRACTED: Mir-124 Attenuates STAT3-Mediated TH17 Differentiation in Colitis-Driven Colon Cancer - Lin, Shiyong; Liu, Qianwen; Wen, Jing; Bai, Kunhao; Guo, Yandong; Wang, Jing (Frontiers in Oncology, 2020)
Backgroud: Inflammation often induces regeneration to repair the tissue damage. However, chronic inflammation can transform temporary hyperplasia into a fertile ground for tumorigenesis. Here, we demonstrate that the miR-124 acts as a safeguard to inhibit the pro-inflammatory production and reparative regeneration. Methods The expression levels of miR-124 and IL-17, IFN-γ were analyzed by quantitative real-time polymerase chain reaction (qRT-PCR). TH17 or TH1 cells were detected by flow cytometer, respectively. the binding of STAT3 to the promoter region of IL-17 gene was analyzed by Chip assay . miR-124 binding to the 3’UTR of STAT3 gene was detected by reported plasmid construction and luciferase assay. Furthermore, DSS-induced colitis mice model and T cell transfer model were used to confirm the function of miR-124 in vivo. The related gene expression was analyzed by ELISA and western blot experiments. Results The results indicated that miR-124a deficiency leads to colon tumorigenesis after Citrobacter rodentium infection and AOM/DSS induced colon cancer murine model. In molecular mechanism, miR-124 targets STAT3 to suppress T helper 17 (TH17) cell differentiation and expansion, and keep TH17 polarization in colonic microenvironment. Conclusions Our study highlights highlight the potential role of miR-124 in the control of immune responses and pathogenesis of inflammatory diseases.